Pengaruh Perubahan Tarif Pajak, Sanksi Perpajakan Dan Kesadaran Pembayaran Pajak Terhadap Kepatuhan Wajib Pajak - Lidya Agustina; Fauziyah Fauziyah; Srikalimah Srikalimah (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
The type of research applied in this research uses quantitative descriptive. This research was carried out at the Kediri City Micro Business and Manpower Service. The research sample for a population of 230 and the 90% confidence level is 70. The results of this study show that the tax rate change variable (X1) has a partially significant effect on taxpayer compliance (Y). This shows that the significant value of the tax rate change variable is 0.001< 0.05, then H1 is accepted and H0 is rejected. The tax sanctions variable (X2) has a partially significant effect on taxpayer compliance (Y). This shows that the significant value of the organizational commitment variable is 0.000 < 0.05, so Ha2 is accepted and H0 is rejected. Tax payment awareness variable (X3 ) has a partially significant effect on taxpayer compliance (Y). This shows that the significant value of the organizational culture variable is 0.000<0.05, so Ha3 is accepted and H0 is rejected. The variables changes in tax rates (X1), tax sanctions (X2) and awareness of tax payments (X3) have a significant effect simultaneously on taxpayer compliance (Y). This is shown by the significant value of the solidarity, organizational commitment and organizational culture variables of 0.000<0.05, then Ha4 is accepted and H0 is rejected.